Pengaruh Lokasi, Harga dan Promosi Terhadap Minat Beli Konsumen Pada Kopi Ketje Lampung - Aditya Sasabila Akbar; Dera Liana Ningrum; M Rait Alparisin (Jurnal Enterpreneur dan Bisnis (JEBI), 2020)
AbstractThis study aims to examine the effect of price, location and promotion on buying interest in ketje Lampung coffee. The method used in research with a questionnaire. The sample of this study may be 41 respondents. Statistical tests were performed using PLS basedStructural Equation Modeling. The validity test uses the loading factor value, while the reliability uses the Cronbach's alpha value, composite reliability and Average Variance Extracted (AVE). All proposed hypotheses are supported and significant. The conclusion of this study is the effect of price, location and promotion has a significant and positive effect on buying interest in Ketje Lampung coffee.Keywords : price, location, promotion and consumer buying interest.